KESESUAIAN SEMA NOMOR 4 TAHUN 2011 YANG MENGATUR EKSISTENSI WHISTLEBLOWER DAN JUSTICE COLLABORATOR TERHADAP UNDANG-UNDANG NOMOR 8 TAHUN 2010 - Ester Johana Elisabeth; Wiwik Afifah (Gapenas Publisher, 2023)
To combat organized crime, including money laundering, whistleblowers and justice partners are involved in the criminal justice system. involve both those who committed the crime and those who reported it, with the reporting witness being someone who was there when the crime was committed. While these offenders are actors ready to assist law enforcement authorities. This paper examines if SEMA No. 4 of 2011, which governs whistleblowers and justice collaborators, and Law No. 8 of 2011 are compatible using normative legal research methodologies with a statutory and conceptual approach. The study's findings indicate that SEMA is the highest regulation governing whistleblowers and justice collaborators because Law No. 8 of 2011 2010 does not regulate them